Shaping women's lives : laws, practices and strategies in Pakistan - Shaheed, Farida; Shirkat Gah. (Lahore : Shirkat Gah, Women's Resource Centre, 1998)
Collection of research papers.
Keywords: Women -- Legal status, laws, etc. -- Pakistan; Women (Islamic law) -- Pakistan; Feminism -- Pakistan